(untitled) (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
The goal that this research will achieve is to examine and validate the impact of corporate social responsibility disclosure, then corporate governance as independent variables and profitability, leverage, firm size, and capital intensity as control variable on tax aggression. This study uses secondary data, including annual reports and sustainability reports that released by firms on the Indonesia Stock Exchange and their own websites. This study’s population consists of mineral and coal mining company registered on the Indonesia Stock Exchange between 2021 and 2023 period. Using the purposive sampling method, this study’s entire sample consists of 28 data points from 37 firms. Data were analyzed by descriptive analysis and multiple regression analysis. The disclosure of corporate social responsibility is measured using 2021 Global Reporting Initiative (GRI) amounted to 117 disclosure item, and the corporate governance is representated by the proportion of independent commissioners and institutional ownership. The findings of this study show that Corporate social responsibility disclosure has a negative and significant effect on tax aggressiveness, whereas the proportion of independent commissioners and the amount of institutional ownership has no significant effect on tax aggressiveness in Indonesian mineral and coal mining companies.